International market selection of Parfois - Guedes, Marta (2017)
Parfois has been internationalizing into many countries and would like to continue growing. This study focuses on the IMS of Parfois, comparing countries from the all around the world, in a quantitative analysis at first, followed by a qualitative analysis. The purpose of the project is to help Parfois select the optimal market for expansion. Through semi structured interviews, literature research, and country clustering and ranking methods South Korea was selected as the best market for expansion, followed by Israel.